Pemberdayaan Masyarakat dalam Pengembangan Program PUSPAGA di Sidotopo Wetan Kenjeran - Zafi Putra Jaelani; Bagus Nuari Harmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Community empowerment has a very crucial and important role in building the foundations of sustainability and prosperity in Indonesia. If the community has carried out community empowerment, then they will not only become beneficiaries, but will also become an active part in the development process. Violence against women and children is an unavoidable incident in big cities like Surabaya. However, this does not mean that the Surabaya City Government is not doing anything to overcome this problem. The Family Learning Center (PUSPAGA) is one of the platforms and facilities offered by the Surabaya City government to its citizens. The research conducted by the author used qualitative methods with a descriptive approach. This method is used to describe and explain precisely the problems that occur. The data obtained in writing this article is divided into two, namely primary data and secondary data. The concept of empowerment is closely related to two concepts, namely the concept of power and the concept of disadvantage or inequality. Community empowerment is also the process of providing resources, knowledge and skills to the community so that they are able to determine their own choices and future. The definition of community empowerment by Jim Ife is explained using four perspectives, namely: pluralist, elitist, structuralist and post-structuralist perspectives. through this PUSPAGA program with assistance from the parties concerned to carry out educational outreach in community activities to take part in PUSPAGA activities. This is done to foster a sense of citizen participation, and to increase public awareness regarding violence against women and children through the PUSPAGA program.